1989
DOI: 10.1161/01.str.20.4.554
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral loss of vision in bright light.

Abstract: We describe four patients with episodic bilateral vision impairment related exclusively to light exposure. Each had angiographically documented bilateral high-grade stenosis or occlusion of the internal carotid arteries. This phenomenon appears to be related to bilateral simultaneous retinal ischemia delaying regeneration of visual pigments in the pigment epithelial layer. It must be distinguished from bilateral occipital lobe ischemia caused by vertebrobasilar system disease. (Stroke 1989;20:554-558)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…27 Present study finds eight miners reported about low vision and six of them reported hearing loss. Low vision might be because of dust 28 or sunlight 29 because miners were exposed to dust and sunlight during work. Worldwide, 16% of the disabling hearing loss in adults is attributed to occupational noise.…”
Section: Discussionmentioning
confidence: 99%
“…27 Present study finds eight miners reported about low vision and six of them reported hearing loss. Low vision might be because of dust 28 or sunlight 29 because miners were exposed to dust and sunlight during work. Worldwide, 16% of the disabling hearing loss in adults is attributed to occupational noise.…”
Section: Discussionmentioning
confidence: 99%
“…80 Due to similarities in clinical presentation CRVO and venous stasis retinopathy due to carotid artery disease can be differentiated by measuring retinal arterial pressure (which is characteristically low in carotid artery stenosis) by ophthalmodynamometry or oculopneumoplethysmography. 86…”
Section: Subacute and Chronic Vascular Diseasesmentioning
confidence: 99%
“…1 Symptoms of ocular ischemia have been reported to occur on a hemodynamic basis also. It has been proposed that symptoms occur when relative perfusion deficits result from the combination of occlusion or stenosis of the ipsilateral internal carotid artery with a hemodynamic stress, 2-4 increased retinal oxygen demand, [5][6][7][8] or bright light amaurosis fugax associated with increased intraocular pressure. 4 Hemodynamic stressors that have been reported in association with transient visual changes include orthostasis associated with postural changes, antihypertensive therapy, or postprandial effects.…”
Section: Discussionmentioning
confidence: 99%